Point Cumana, Trinidad - (:unkn) unknown (Wilsons Limited, Trinidad, 2009)
This is a painting of Point Cumana on Trinidad's west coast, showing the wooded coastline and the calm blue waters of the Gulf of Paria.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Point Cumana; Coasts--Trinidad and Tobago; Seashore--Trinidad and Tobago; Paria, Gulf of (Venezuela and Trinidad and Tobago); Trees--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Dwellings--Trinidad and Tobago; [1912]